Comparison of the Efficacy of D2 Gastrectomy Plus Liver Radiofrequency Combined With Chemotherapy Versus Chemotherapy Alone in the Treatment of Advanced Gastric Cancer With Unresectable Synchronous Liver Metastases: A Multicenter Randomized Controlled Trial Protocol - Wang, Weidong; Gao, Ruiqi; Yu, Pengfei; Mo, Zhenchang; Dong, Danhong; Yang, Xisheng; Li, Xiaohua; Ji, Gang (Frontiers in Oncology, 2022)
Background Whether patients with advanced gastric cancer with unresectable synchronous liver metastases require surgical treatment remains a controversial topic among surgeons. Recently, an open-label multicenter, international RCT study show that compared with chemotherapy alone, gastric resection combined with chemotherapy had no survival advantage for advanced gastric cancer with unresectable synchronous liver metastases. A limitation of this study was that gastrectomy for gastric cancers was restricted to D1 lymphadenectomy and no metastatic lesions were removed. Whether D2 gastrectomy plus liver radiofrequency plus postoperative chemotherapy could provide benefits to these patients is worthy of further confirmation by high-level evidence-based medicine. Methods/Design This study will investigate the efficacy of D2 gastrectomy plus liver radiofrequency plus postoperative chemotherapy compared to chemotherapy alone in a prospective, multicenter, randomized controlled trial that will enroll 200 patients who have advanced gastric cancer with unresectable synchronous liver metastases. The patients will be randomly divided into two groups: the test group (D2 gastrectomy plus liver radiofrequency plus postoperative chemotherapy, n=100) and the control group (chemotherapy alone, n=100). The patients’ general information, past medical history, laboratory tests, imaging results, surgery details, and chemotherapy details will be recorded and analysed. The overall survival (OS) will be recorded as primary endpoints. Progression-free survival (PFS) and the total incidence of complications will be recorded as secondary endpoints. Discussion This study is to establish a multicentre randomized controlled trial to compare the efficacy of D2 gastrectomy plus liver radiofrequency combined with postoperative chemotherapy versus chemotherapy alone. Trial Registration Chinese Clinical Trial Registry, Approved No. of ethics committee:ChiECRCT20200331. Registered on 15 November 2020. Registration number:ChiCTR2000039964. The study has received full ethical and institutional approval. Advantages and Limitations of this Study This is the first clinical trial that will provide evidence on the efficacy of D2 gastrectomy plus liver radiofrequency combined with chemotherapy versus chemotherapy alone for the treatment of advanced gastric cancer with unresectable synchronous liver metastases. A prospective RCT with 200 patients who have advanced gastric cancer with unresectable synchronous liver metastases. Clinical Trial Registration [https://www.chictr.org.cn/], identifier ChiCTR2000039964.